CAMBIOS EN EL COLOR DURANTE EL BENEFICIO DEL GRANO DE CACAO (Theobroma cacao L.) PERUANO PROCEDENTE DE PIURA - Chire, Gabriela C. (2017)
Through this research which aim is to relate the color variations of cocoa beans during the fermentation, drying and harvest time process, in an iqual time of cocoa pods storage. Was used for this evaluation the CIELAB system, which define the color as physical index and color model (L*, a* and b*), then was calculated color change (∆E*), at measure were giving the biochemical changes during the fermentation and drying process in cocoa beans of Cultivar Nativo from Piura. The average values of color for L* were 52,03 to 34,05; a* were 12,64 to 14,69 and for b* were 12,59 to 5,15 being variance non-significative for fermentation process of Cultivar Nativo cocoa beans during post-harvest. It is concluded ∆E* is different in drying for both harvest time (p<0,05) due to climatic conditions.